1970
DOI: 10.1139/p70-001
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic rotation spectrum of glyoxal

Abstract: Twenty-one bands of the first triplet-singlet system of glyoxal (3A,-'A,) have been photographed in absorption and in magnetic rotation using high resolving power. Analysis yields the following vibrational frequencies for the molecule in the 3A, state: v2 = 1458.9 cm-', v4 = 963., cm-', v5 = 502., cm-', v, = 234.3 cm-', and v12 = 391., cm-'. These frequencies are very similar to those for glyoxal in the corresponding ' A , excited state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…King [15] and Paldus & Ramsay [16] in rotational analyses of the 4550 A absorption have shown unambiguously that the symmetry of the excited state is A,, and that the polarization of the transition is z (perpendicular to the molecular plane). Recently, the magnetic rotation spectrum of the 5200 A band has been examined and shown to have a vibrational structure that is very similar to that of the singlet-singlet system [17]. The transition from the antisymmetric nonbonding orbital to the lowest 7c* MO is forbidden, resulting in an excited state with B, symmetry.…”
Section: Fig 2 Energy Of Two Highest Occufiied Molecular Orbitals Imentioning
confidence: 99%
“…King [15] and Paldus & Ramsay [16] in rotational analyses of the 4550 A absorption have shown unambiguously that the symmetry of the excited state is A,, and that the polarization of the transition is z (perpendicular to the molecular plane). Recently, the magnetic rotation spectrum of the 5200 A band has been examined and shown to have a vibrational structure that is very similar to that of the singlet-singlet system [17]. The transition from the antisymmetric nonbonding orbital to the lowest 7c* MO is forbidden, resulting in an excited state with B, symmetry.…”
Section: Fig 2 Energy Of Two Highest Occufiied Molecular Orbitals Imentioning
confidence: 99%
“…It was also found that upon electronic excitation to the lowest singlet and triplet electronic states, the trans-conformers of glyoxal [12,13] and oxalyl halides [14][15][16][17][18][19][20], as well as the cis-conformer of glyoxal (upon singlet-singlet excitation) [21], keep a planar structure. However, no data on the structure of the second conformers of oxalyl halides in excited electronic states are available.…”
Section: Introductionmentioning
confidence: 99%
“…The ' A,-' A, (.n *-n) and A,-' A, (.n *-n) band systems of glyoxal with 0-0 bands at 4550 A and 5207 A, respectively, have been studied in considerable detail in absorption (Brand 1954;King 1957 ;Paldus and Ramsay 1967 ;Birss et al 1970), in emission (Brand 1954, and earlier references cited therein; Holzer and Ramsay 1970), and in magnetic rotation (Eberhardt and Renner 1961 ;Goetz, McHugh, and Ramsay 1970). Recently, a new band system, consisting of seven bands, was observed in the emission induced in glyoxal by the lines of an argon ion laser (Holzer and Ramsay 1970).…”
Section: Introductionmentioning
confidence: 99%